Faktor-Faktor yang Menentukan Pemilihan Teknik Pengolahan Tanah pada Usahatani Padi - Sri Hery Susilowati; Pantjar Simatupang (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 1990)
The main objective of this paper is the examine the factor influencing tractor utilization in rice form study was conducted in four village of East Java in crop season 1988-1989. Based on the logit analyses, it was shown that the probability of farmer using tractor was significanly influenced by cropping intensity and the ratio of tractor rental value to holing wage. Moreover, the rental rate of tractor shows a positive impact to the probablity of adapting tractor.